Simbolika dogajalnega prostora v Matkovi Tini, Sreči in Krstu pri Savici - Božič, Zoran (Jezik in slovstvo, 2000)
The typical settings in Matkova Tina, Sreča (Happiness) and Krst pri Savici (The Baptism by the Savica) is locations near a water. Water symbolically bathes away guilt of the central characters, i.e. the innkeeper's Tina, Strežkova Tinka and Črtomir, who all yearned for love but ended up as outcasts and doers of action with fatal consequences. Tina, Tinka and Črtomir did the stations along the river Soča. The river is marked by the figure of the Christian saint John Nepomuce, protector against swollen waters, who sacrificed his life so that a borbidden love could live on.
Keywords: Prešeren, France, 1800-1849; Pregelj, Ivan, 1883-1960; Kosmač, Ciril, 1910-1980; Slovene literature; slovenska književnost; literarni motivi; literarne študije; voda; Prešeren, France: Krst pri Savici; Pregelj, Ivan: Matkova Tina; Kosmač. Ciril: Sreča